The Randstad as a Network City - Jan Ritsema van Eck; Femke Daalhuizen; Lia Van den Broek; Frank Van Oort; Otto Raspe (European Regional Science Association (ERSA), 2005)
Randstad Holland, the most urbanised area in the western part of the Netherlands, is one of the seven World Cities that were described in Peter Halls famous study of that name. World cities are those cities which have the highest level (in terms of both quantity and quality) of internationally oriented activities. In this ranking of world cities, the Randstad is often mentioned as an example of a polycentric metropolis. But does the Randstad function as one world city, rather than a conglomerate of medium-sized urban regions in close proximity to each other? The network city is supposed to be more than the sum of the constituent urban regions. This implies not only specialisation between these urban regions, but also complementarity and, as a result of this, a high quality (metropolitan) environment for residents, visitors and business. Clearly, the four main urban regions of the Randstad show some degree of functional specialisation. In this paper, the main focus will be on the complementarity. We propose to measure complementarity by analysing flows of people, goods and/or information, specifically focussing on the asymmetric flows, against the background of functional specialisation. Some results are presented for the Randstad Holland as well as some other polycentric urban networks, which are discussed in the context of the debate about the Randstad as a Network City.
Keywords: 330